Religious Attendance and Covid-19. Evidences from Italian Regions - Vincenzo Alfano; Salvatore Ercolano; Gaetano Vecchione (Center for Economic Studies and Ifo Institute (CESifo), 2020)
By changing many aspects of everyday life, the COVID-19 pandemic and the social distance policies implemented to face it have affected the behaviour of many people, all over the world. Has the pandemic also affected people approach toward the divine? Previous evidences suggest that the prayer search over the Internet rose during the pandemic and that people tend to mainly rely on intrinsic religiosity rather than extrinsic to cope with adversity. In this contribution, by the means of a set of panel random effect estimators, we compare the change in religious attendance in Italian regions before and during the pandemic. Our results suggest that there is an increase in religiosity during the Covid-19 pandemic. Our findings are robust to several specifications of the model and to different estimators. This suggest that people derive more comfort from extrinsic religious activities during hard times, characterized by uncertainty.
Keywords: Z12; N34; I12; 330; COVID-19; coronavirus; religious attending; mass; mass streaming